Synthesis and Dual 5-HT1A/SSRI Activities of Some Novel Arylpiperazine Derivatives of Duloxetine - Chen, Shao-Rui; Li, Ai-Jun; Chen, Ming-Ming (Asian Journal of Chemistry, 2011)
A series of novel arylpiperazine derivatives of duloxetine were designed and synthesized from the key intermediate 5 by acylation, alkylation and reduction based on 5-HT1A/SSRI drugs design strategies. Compound 5 was obtained through the reaction sequence including condensation, reduction, O-etherification, Von Braun reaction, hydrolysis reaction. Structures of the synthesized compounds were confirmed by MS, 1H NMR and HRMS. Furthermore, these compounds were evaluated for their dual 5-HT1A/5-HTT activities. The results indicated that all the compounds exhibited certain affinity to 5-HTT and 5-HT1A receptor.